Post-pedagogical Syndrome of the Digimodernism Age - I. A. Kolesnikova (Высшее образование в России)
The article discusses the influence of Metamodern culture and digitalization of education on the transformation of the pedagogical understanding of learning process. The author relies on the post-postmodern age interpretations presented in the works of S. Abramson, M. Epstein, R. Eschelman, A. Kirby, J. Mensch, P. Samuels, L. Turner, T. Vermeulen and R. Van den Acker; the transdisciplinary (B. Nicholescu) and connectivist (D. Cormier, G. Siemens) approaches and international documents about the education development in a complex society. In the Metamodern epoch under the influence of the universal digitalization there have been signs indicating that the theory and practice of learning has gone beyond the enduring some pedagogical meanings. This is being manifested at the level of the spontaneous transformation of the main components of learning process; changes in the pedagogical thesaurus, the emergence of “hybrid” didactic theories. The author defines this phenomenon as the post-pedagogical syndrome of the digital age which is capable to disrupt the historical continuity of educational culture. The article talks about the lack of resources in modern pedagogical science to explain the realities of lifelong education as a part of the Digimodernism culture and to develop the truly innovative ways of teaching. The author has suggested that the creation of effective methods of teaching and self-education in the digital age is possible only in the case of rethinking and reassessment of basic didactic categories and concepts on a transdisciplinary basis, taking into account the pedagogical experience of the analogical era and preserving the continuity of humanitarian values and meanings. The author’s arguments and conclusions are addressed to supporters of the study of education on an interdisciplinary and transdisciplinary basis.